Play therapy and Asperger's syndrome helping children and adolescents grow, connect, and heal through the art of play - Hull, Kevin B. 1971- (Jason Aronson, 2011)
"Play Therapy and Asperger's Syndrome Helping Children and Adolescents Grow, Connect, and Heal Through the Art of Play" discusses play therapy techniques for children and adolescents diagnosed with Asperger's syndrome in a simple, clear manner. It is designed to help mental health professionals as well as graduate students effectively work with children and adolescents and their families, helping them gain better self-understanding, relationship skills, and emotional growth through the miracle of play"--Provided by publisher.